2012
DOI: 10.3109/09513590.2012.738724
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial, breast and liver safety of soy isoflavones plus Lactobacillus sporogenes in post-menopausal women

Abstract: A 12 months treatment with a nutraceutical compound based on isoflavones and Lactobacillus sporogenes at the recommended doses is safe for endometrium, mammary glands and liver function in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 40 publications
0
36
0
1
Order By: Relevance
“…The mean difference in MD% was 0.69% for all women combined (−1.10% in postmenopausal women and 1.83% in premenopausal women) (6). No significant differences in mammographic density between soy and placebo groups were reported in two other trials that supplemented soy isoflavones or placebo for 10 months (32 soy vs 34 placebo) (43) and 12 months (65 soy vs 65 placebo) (44). …”
Section: Discussionmentioning
confidence: 87%
“…The mean difference in MD% was 0.69% for all women combined (−1.10% in postmenopausal women and 1.83% in premenopausal women) (6). No significant differences in mammographic density between soy and placebo groups were reported in two other trials that supplemented soy isoflavones or placebo for 10 months (32 soy vs 34 placebo) (43) and 12 months (65 soy vs 65 placebo) (44). …”
Section: Discussionmentioning
confidence: 87%
“…For the evaluation, EFSA selected 43 human studies and 62 animal studies. Among these studies were four epidemiological studies investigating breast cancer incidence (Rebbeck et al , ; Obi et al , ; Brasky et al , ; Boucher et al , ), eight interventional controlled studies, measuring mammographic density (Morabito et al , ; Atkinson et al , ; Marini et al , ; Powles et al , ; Verheus et al , ; Maskarinec et al , ; Colacurci et al , ; Delmanto et al , ), and two interventional controlled studies, investigating histopathological changes (Cheng et al , ; Khan et al , ). These studies did not reveal an association between isoflavone exposure and adverse effects in the mammary gland (EFSA ANS Panel, ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, soy isoflavone tablets easily allow intake in excess of 100 mg isoflavones/d, five times that of isoflavone intake from typical Asian diets 1 . One long-term (3 y) study 2 indicated that soy isoflavone (extract form) intake was safe for the endometrium and breast, another (2 y) study 3 demonstrated that soy hypocotyl isoflavones (80 or 120 mg) did not adversely affect endometrial thickness, and another recent (1 y) study 4 showed that soy isoflavones (60 mg) combined with Lactobacillus sporogenes was safe for the endometrium, mammary glands, and liver function. Indeed, a 2-y study 5 indicated that genistein (54 mg/d), the predominant soybean isoflavone, reduced the mean number of hot flushes/d, but it did not affect the endometrium.…”
Section: Introductionmentioning
confidence: 99%